Pseudomonas aeruginosa‐dependent upregulation of TLR2 influences host responses to a secondary Staphylococcus aureus infection. Issue 2 (2nd September 2013) - Shin, Hee‐Sung; Lee, Jung‐Hoon; Paek, Se‐Hwan; Jung, Yong Woo; Ha, Un‐Hwan
Abstract: The clinical impact of polymicrobial infections has received increasing attention from the medical community. However, the potential effects of Pseudomonas aeruginosa infection on the development of host responses against Gram‐positive bacteria, such as Staphylococcus aureus, are unknown. Here, P. aeruginosa infection was found to induce the expression of Toll‐like receptor 2 (TLR2), which plays a dominant role in sensing pathogen‐associated molecular patterns (PAMPs) expressed by Gram‐positive bacteria. P. aeruginosa ‐dependent upregulation of TLR2 was not mediated by flagellin, or by the type III (T3SS) or type VI (T6SS) secretion systems, but was upregulated by lipopolysaccharide (LPS). Upregulation of TLR2 influenced the magnitude of proinflammatory responses to the secondary S. aureus infection, but there was no clear effect on phagocytosis of S. aureus by macrophages. Taken together, the results of this study demonstrate that P. aeruginosa infection results in the upregulation of TLR2 expression, subsequently enhancing innate immune responses against a secondary S. aureus infection. Abstract : The clinical impact of polymicrobial infections has increasingly recognized in recent years. In this study the impact of a P. aeruginosa infection on a secondary S. aureus was studied. The findings are intriguing since it was demonstrated that the primary P. aeruginosa infection upregulated TLR2 expression thereby enhancing innate immune responses against the secondary S. aureus infection.